Model of MSME Digital Marketing through for Biopharmaceutical Products - Marselina Endah Hiswati; Putra Wanda; I Wayan Ordiyasa; Lila Retnani Utami; Supardi RS; Rainbow Tambunan (Universitas Respati Yogyakarta, 2023)
Sleman Regency has more than 50 traditional markets and also a variety of MSME business and there are more than 18,293 accommodation, food and beverage business sectors that are developing. Mobile-based information technology is urgently needed as a medium that supports efforts to promote and market MSME products, especially traditional culinary products, in this case processed products of Biopharmaca plants. The existence of a social restriction policy due to the COVID-19 pandemic requires the public to recognize technology as a medium of socialization towards digitalization. Thus, a mobile-based application is needed as a meeting place for sellers and buyers specifically for local Sleman products. Digital innovation has an impact on increasing the income and economy of MSME actors in Sleman Regency, Special Region of Yogyakarta